The Impact of TARP Capital Infusion on Bank Liquidity Creation: Does Bank Size Matter? - Zheng, Chen; Cheung, Adrian Wai Kong; Cronje, Tom (Association of the International Journal of Central Banking, 2022)
This paper uses the Troubled Asset Relief Program (TARP) to examine whether the effect of capital support on bank liquidity creation differs depending upon bank size. We find that the relationship between TARP and liquidity creation is positive for small banks, but the relationship is insignificant for large banks. Further analysis shows that the positive and highly significant effect of TARP on small banks’ liquidity creation may take longer to materialize, and that this increase in liquidity creation is experienced only by small TARP banks that did not repay early. We also find that the positive effect of TARP is driven mainly by the asset-side (on-balance-sheet) liquidity creation of small banks, and that this effect holds in most lending categories. These findings yield important policy implications for bank bailouts.